The Multiplicity of Nontrivial Solutions for a New px-Kirchhoff-Type Elliptic Problem. (19th June 2021) - Chu, Chang-Mu; Xiao, Yu-Xia
Abstract : In the paper, we study the existence of weak solutions for a class of new nonlocal problems involving a p x -Laplacian operator. By using Ekeland's variational principle and mountain pass theorem, we prove that the new p x -Kirchhoff problem has at least two nontrivial weak solutions.